Metal@COFs: Covalent Organic Frameworks as Templates for Pd Nanoparticles and Hydrogen Storage Properties of Pd@COF-102 Hybrid Material - Kalidindi, Suresh Babu; Oh, Hyunchul; Hirscher, Michael; Esken, Daniel; Wiktor, Christian; Turner, Stuart; Van Tendeloo, Gustaaf; Fischer, Roland A. (Chemistry : a European journal, 2012)
Three‐dimensional covalent organic frameworks (COFs) have been demonstrated as a new class of templates for nanoparticles. Photodecomposition of the [Pd(η3‐C3H5)(η5‐C5H5)]@COF‐102 inclusion compound (synthesized by a gas‐phase infiltration method) led to the formation of the Pd@COF‐102 hybrid material. Advanced electron microscopy techniques (including high‐angle annular dark‐field scanning transmission electron microscopy and electron tomography) along with other conventional characterization techniques unambiguously showed that highly monodisperse Pd nanoparticles ((2.4±0.5) nm) were evenly distributed inside the COF‐102 framework. The Pd@COF‐102 hybrid material is a rare example of a metal‐nanoparticle‐loaded porous crystalline material with a very narrow size distribution without any larger agglomerates even at high loadings (30 wt %). Two samples with moderate Pd content (3.5 and 9.5 wt %) were used to study the hydrogen storage properties of the metal‐decorated COF surface. The uptakes at room temperature from these samples were higher than those of similar systems such as Pd@metal–organic frameworks (MOFs). The studies show that the H2 capacities were enhanced by a factor of 2–3 through Pd impregnation on COF‐102 at room temperature and 20 bar. This remarkable enhancement is not just due to Pd hydride formation and can be mainly ascribed to hydrogenation of residual organic compounds, such as bicyclopentadiene. The significantly higher reversible hydrogen storage capacity that comes from decomposed products of the employed organometallic Pd precursor suggests that this discovery may be relevant to the discussion of the spillover phenomenon in metal/MOFs and related systems. In the frame: Pd@COF‐102 hybrid material (COF=covalent organic framework; see figure) is a rare example of a metal‐nanoparticle‐loaded porous crystalline material with a very narrow size distribution, cavity size matching, and an absence of larger agglomerates even at high loadings (30 wt %). Hydrogen storage studies showed that the H2 capacities were enhanced by a factor of 2–3 as a result of Pd impregnation on COF‐102 at room temperature and 20 bar.